2019
DOI: 10.1155/2019/4265782
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of AO/OTA 43-C3 Pilon Fracture: Be Aware of Posterior Column Malreduction

Abstract: Treatment of pilon fractures remains challenging due to the difficulty of fracture reduction and associated soft tissue complications. The aim of this study was to evaluate the pitfalls and strategies of posterior column reduction in the treatment of complex tibial pilon fractures (AO/OTA 43-C3). Thirteen AO/OTA classification 43-C3 type pilon fractures treated between January 2013 and January 2016 were retrospectively analyzed. Nine cases were treated by external fixation within 26 hours (range, 6–56 hours) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In these articles, the outcomes were reported as the total number of the complication of interest for 1 treatment group compared with another treatment group, but without distinction as to whether the complication occurred in AO 43-C1 or AO 43-C3 injury or the status of the skin at the time of injury. The remaining 13, with 8 articles reporting a staged approach [3,15,[24][25][26][27][28][29] and 5 articles pertaining to primary arthrodesis [8,[20][21][22][23] were evaluated and analyzed. The 13 studies examined in this review included 377 total fractures, 228 of which involved AO 43-C3 pilon fractures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these articles, the outcomes were reported as the total number of the complication of interest for 1 treatment group compared with another treatment group, but without distinction as to whether the complication occurred in AO 43-C1 or AO 43-C3 injury or the status of the skin at the time of injury. The remaining 13, with 8 articles reporting a staged approach [3,15,[24][25][26][27][28][29] and 5 articles pertaining to primary arthrodesis [8,[20][21][22][23] were evaluated and analyzed. The 13 studies examined in this review included 377 total fractures, 228 of which involved AO 43-C3 pilon fractures.…”
Section: Resultsmentioning
confidence: 99%
“…The authors classified treatment groups in the included studies according to the use of fusion procedures. Five studies [8,[20][21][22][23] used fusion procedures, 8 studies used other types of treatment [3,15,[24][25][26][27][28][29] (Table 1). Weighted analysis, using sample sizes reported in each article, was used to compare these 2 patient groups on key indices.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of posterolateral fragment, reduction and temporary fixation of the posterolateral fragment is recommended as the first step of the articular reduction. 13 Guan et al 3 reported satisfactory results with the use of the combined posterolateral and anterior approach which posterior cortical reduction takes the first place. Ketz and Sanders 4 conclude that proper reduction of the posterolateral fragment is a reference point for the remainder of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pilon fractures are classified according to the Ruedi and Allgower system and the OTA/AO fracture classification system. Ruedi and Allgower split the tibial ceiling fracture into three types based on their displacement and comminution level from the articular surface (Figure 6) [1], [21], [22].…”
Section: Classificationsmentioning
confidence: 99%